Application of DNA-Binding Protein Prediction Based on Graph Convolutional Network and Contact Map. (17th January 2022) - Lu, Weizhong; Zhou, Nan; Ding, Yijie; Wu, Hongjie; Zhang, Yu; Fu, Qiming; Li, Haiou
Abstract : DNA contains the genetic information for the synthesis of proteins and RNA, and it is an indispensable substance in living organisms. DNA-binding proteins are an enzyme, which can bind with DNA to produce complex proteins, and play an important role in the functions of a variety of biological molecules. With the continuous development of deep learning, the introduction of deep learning into DNA-binding proteins for prediction is conducive to improving the speed and accuracy of DNA-binding protein recognition. In this study, the features and structures of proteins were used to obtain their representations through graph convolutional networks. A protein prediction model based on graph convolutional network and contact map was proposed. The method had some advantages by testing various indexes of PDB14189 and PDB2272 on the benchmark dataset.